Enhancing Islamic Religious and Character Education through a Deep Learning Approach - Nestri Natasya Nilpendra; Roni Faslah; Neni Triana; Nursuadila Nursuadila; Maya Ramadhani (STIT Ahlussunnah Bukittinggi, 2026)
Islamic Religious Education and Character learning in the era of the Industrial Revolution 4.0 and Society 5.0 faces complex challenges in balancing the transmission of authentic Islamic teachings with the need for creativity, collaboration, critical thinking, and digital literacy. Conventional approaches that emphasize memorization are often insufficient in fostering strong spiritual character. This study aims to explore the implementation of the Deep Learning approach in Islamic Religious Education and Character learning, focusing on how its principles mindful, meaningful, and joyful learning enhance students’ spiritual understanding and character development. This study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, classroom observations, and documentation to obtain comprehensive insights into the application of Deep Learning principles. The data were analyzed through thematic interpretation to identify patterns of implementation and their impact on learning processes. The findings indicate that constructivist-based lesson planning encourages students to develop a deeper and more contextual understanding of Islamic teachings. The implementation of Deep Learning principles through reflective discussions and experiential practices enhances students’ spiritual awareness, value internalization, and real-life application. However, challenges such as limited instructional time and the need for pedagogical adaptation were also identified. The study implies that the Deep Learning approach has significant potential to transform Islamic Religious Education into a more meaningful, student-centered learning process. It contributes to strengthening character education and supports the development of students who are both religiously grounded and adaptable to contemporary challenges.